The giant E3 ligase HUWE1 is linked to tumorigenesis, spermatogenesis, intellectual disability, and inflammatory diseases - Qi, Lu; Xu, Xiaoqing; Qi, Xiaopeng (Frontiers in Cellular and Infection Microbiology, 2022)
E3 ubiquitin ligases determine the substrate specificity and catalyze the ubiquitination of lysine residues. HUWE1 is a catalytic HECT domain-containing giant E3 ligase that contains a substrate-binding ring structure, and mediates the ubiquitination of more than 40 diverse substrates. HUWE1 serves as a central node in cellular stress responses, cell growth and death, signal transduction, etc. The expanding atlas of HUWE1 substrates presents a major challenge for the potential therapeutic application of HUWE1 in a particular disease. In addition, HUWE1 has been demonstrated to play contradictory roles in certain aspects of tumor progression in either an oncogenic or a tumor-suppressive manner. We recently defined novel roles of HUWE1 in promoting the activation of multiple inflammasomes. Inflammasome activation-mediated immune responses might lead to multifunctional effects on tumor therapy, inflammation, and autoimmune diseases. In this review, we summarize the known substrates and pleiotropic functions of HUWE1 in different types of cells and models, including its involvement in development, cancer, neuronal disorder and infectious disease. We also discuss the advances in cryo-EM-structural analysis for a functional-mechanistic understanding of HUWE1 in modulating the multitudinous diverse substrates, and introduce the possibility of revisiting the comprehensive roles of HUWE1 in multiple aspects within one microenvironment, which will shed light on the potential therapeutic application of targeting giant E3 ligases like HUWE1.